2008
DOI: 10.2353/ajpath.2008.070391
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Model of Acute Humoral Rejection of Renal Allografts Associated with Concomitant Cellular Rejection

Abstract: Acute humoral rejection (AHR), which occurs in up to 8% of kidney transplant recipients, is a significant cause of renal allograft dysfunction and loss. More efficacious treatment modalities are needed to eliminate or curtail alloantibody production and its deleterious effects on the kidney. The availability of animal models mimicking human AHR is essential to understand its pathophysiology and develop new treatment strategies. Using a mouse kidney transplant model, we demonstrate that presensitization of reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 30 publications
6
27
1
Order By: Relevance
“…We have previously described a mouse model of mixed AMR in which B6 hosts are primed to DBA/2 alloantigens with a DBA/2 skin allograft 14 to 21 days prior to receiving a DBA/2 renal allograft (11). As shown in Figure S1, identical results were obtained with recipients primed to donor alloantigens at times ranging from 11–91 days prior to kidney transplantation, indicating that the time of renal transplantation relative to the priming stage was not critical.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously described a mouse model of mixed AMR in which B6 hosts are primed to DBA/2 alloantigens with a DBA/2 skin allograft 14 to 21 days prior to receiving a DBA/2 renal allograft (11). As shown in Figure S1, identical results were obtained with recipients primed to donor alloantigens at times ranging from 11–91 days prior to kidney transplantation, indicating that the time of renal transplantation relative to the priming stage was not critical.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that DSA-producing cells should be presensitized in AAMR. Bickerstaff et al 21 reported that depletion of pre-sensitized CD8 ± T cells had no effect on AAMR model of mouse renal transplantation. However, further studies are required to evaluate which type of presensitized cell is indispensable to AAMR.…”
Section: Discussionmentioning
confidence: 98%
“…and many of the inflammatory cells are in the PTCs but those cells are not infiltrating tubules at the time of AAMR in mouse renal transplantation model 21. …”
mentioning
confidence: 99%
“…What is not directly addressed by the current study is the question of whether CMV reactivation contributes to rejection. In our model, allograft survival (~10–11 days, not shown) was not shorter than historical controls (15), but it is important to note that this model is biased toward rapid rejection, so CMV reactivation may have inadequate time to contribute to this process, particularly because reactivation appears to occur after the rejection episode. Interestingly, using a model of induced cardiac allograft tolerance (without ongoing immunosuppression), we have recently shown that cardiac allograft acceptance is disrupted when recipients are latently infected with CMV, and this disruption is associated with MCMV reactivation (16).…”
Section: Discussionmentioning
confidence: 82%